Citrulline production and protein homeostasis. Issue 5 (September 2019) - Ginguay, Antonin; De Bandt, Jean-Pascal
Abstract : Purpose of review: Protein homeostasis is crucial for maintaining cell functions. Citrulline, an endogenous amino acid, is considered as an efficient source of arginine at systemic and cellular level. Accumulating evidence, obtained from citrulline supplementation studies, suggest anabolic properties especially in malnourished rodents and human. Although these studies might suggest a key role for citrulline in protein homeostasis, the supraphysiological concentrations of citrulline do not allow to conclude on a physiological role. This review aimed to assess the role of endogenous citrulline production on protein homeostasis. Recent findings: According to recent studies, endogenous citrulline, through its regulating effect on nitric oxide production, seems to play a key role in regulating endothelial and immune functions. We can assume that citrulline-dependent endothelial vasodilation could improve organ perfusion and thus amino acid and insulin supply. Furthermore, citrulline regulates immune cells and thus could regulate inflammation and indirectly protein metabolism. Summary: Although we have currently no direct evidence of a regulating role of endogenous citrulline production on protein homeostasis, we can hypothesize that physiologically through its role in endothelial and immune function, citrulline could indirectly participate to protein homeostasis.